Visual Communication In Tourism Development (Study on Curug Cay Waterfall Tourism, Bukit Village, Semidang Lagan District, Central Bengkulu Regency) - Giri Hartono; Vethy Octaviani; Martha Heriniazwi D (Penerbit Jurnal Indonesia, 2024)
This research aims to determine visual communication in tourism development in Bukit Village, Semidang Lagan District, Central Bengkulu Regency. Data collection techniques were carried out using interviews with research informants. The informant in this research was 1 informant, namely the social account manager for the Curug Cay waterfall. The data analysis technique uses qualitative descriptive analysis which consists of data reduction, presentation and conclusions. The research results show that visual communication in tourism development in Bukit Village, Semidang Lagan District, Central Bengkulu Regency is seen based on the Aesthetic Theory according to Dake (2015:98) which consists of Disambiguity and Meaning, Control of Direction, Tension, Unity and Realism. It can be seen that the visual communication carried out by Bukit Village in promoting the Curug Cay waterfall tourist attraction is through social media such as Facebook, Instagram and TikTok. In creating content, there are many things that must be considered, such as strategies for taking interesting pictures and videos so that they attract people's attention to visit the Curug Cay waterfall tourist spot.